Indonesia Paradox on Plastic Waste Import in International Policy and Social Movement Perspective - Idris, Siti Hafsyah; Puteri, Dina Silvia; Wahono, Denita Cahyanti; Firdaus, Rr. Jannatul; Pratomo, Nathanael Bayu Ajie (Universitas Negeri Semarang, 2024)
Indonesia, recognized as the second largest marine polluter globally, faces a significant environmental crisis despite stringent international policies and vigorous social movements advocating for sustainability. According to data from INAPLAS and BPS, Indonesia generates 64 million tons of plastic waste annually, with 3.2 million tons ending up in the sea. The waste management system in Indonesia is rudimentary, involving basic stages of collection, transportation, and disposal, with processing occurring only at the final destination. Amidst this waste crisis, Indonesia continues to import plastic waste from countries such as the United States, Germany, Australia, and Hong Kong, exacerbating the environmental and health hazards. This paper explores the paradox of plastic waste import in Indonesia, focusing on how international policies, including the Basel Convention and its recent amendments, intersect with local regulations and their enforcement. It also examines the role of social movements in combating plastic waste imports and advocating for environmental sustainability. The central problem addressed is the regulatory and social polemic surrounding waste importation in Indonesia, considering the social, political, and legal dimensions. Employing a conceptual and statute approach, the paper provides a comprehensive analysis of the waste import regulation issues linked to social problems within Indonesian society. It argues that the complexity of international trade, economic incentives, and insufficient regulation enforcement contribute to the paradoxical situation where policies and advocacy efforts seem misaligned with outcomes. The findings offer social and juridical recommendations for the Indonesian government and society to address the waste import dilemma effectively. By aligning policies with environmental goals and leveraging social movements, Indonesia can drive significant change towards sustainable waste management practices.